53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady PSP Measurement of Transonic Buffet on a Wing

Abstract: In this study, unsteady pressure field caused by transonic buffeting phenomena on a generic transport model was analyzed using unsteady PSP. The tests were conducted in the JAXA 2-m Transonic Wind Tunnel at M=0.85 and the model angle of attack was varied between 2.5 and 6.8 degrees. From the obtained unsteady PSP data, the RMS of pressure fluctuation was calculated to detect the areas with strong shock oscillation. Spectral analysis was also conducted in order to find frequencies of shock oscillation and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
(8 reference statements)
5
17
0
Order By: Relevance
“…10c, Fig. 12, Sartor and Timme [32], and Sugioka et al [17]), while the tendency with the Mach number is less clear and needs further study. Furthermore, a convective behavior is found at the buffet Strouhal number on the wing for all models.…”
Section: A Strouhal Numbers and Convection Velocities Summarymentioning
confidence: 95%
See 2 more Smart Citations
“…10c, Fig. 12, Sartor and Timme [32], and Sugioka et al [17]), while the tendency with the Mach number is less clear and needs further study. Furthermore, a convective behavior is found at the buffet Strouhal number on the wing for all models.…”
Section: A Strouhal Numbers and Convection Velocities Summarymentioning
confidence: 95%
“…This phenomenon is known as buffet offset [8,15,16]. Sugioka et al [17], Lawson et al [18], and Koike et al [19] performed experimental tests at high M − α, but the same effect was not observed for the 3D buffet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These researches also revealed that the large difference of the peak frequencies [8][9][10] . Furthermore, we clarify the difference of the effect of the vortex generators (VGs) on the unswept and the swept wing.…”
Section: Introductionmentioning
confidence: 93%
“…These techniques are being developed by many organizations and researchers in order to analyze the unsteady issues in aerospace engineering 3,9,10,[13][14][15][16] . Unsteady experimental data are essentially important to validate these methods.…”
Section: Introductionmentioning
confidence: 99%